OPINIONS AND BEHAVIOR OF STUDENTS ABOUT ABUSE OF INTERNET IN SOCIAL INVOLVMENTS: GENDER ANALYSIS - Jošanov, Borislav; Pucihar, Andreja; Jošanov-Vrgović, Ivana; Marošan, Zoran (International Journal of Economic Practice and Policy, 2016)
New Internet technologies brought new gamma of interests worldwide. In the focus of people are social networks, main usage and the abuse of Internet usage. Authors analyze the group of students in Higher School for Professional Business Studies in in Novi Sad, Serbia, and in Faculty of Organizational Sciences Kranj, Slovenia. In the focus of this research are opinions and behavior of students about social aspects of Internet general usage, and specificly opinions about social networks and WikiLeaks. This paper is the succesor of the sross-cultural research that was presented in this journal with the same data two years ago, but structured diferently, acording to the location where they were taken. Results of this research are analyzed and presented according to the gender of examinees.